Simultaneous degradation of anionic and cationic dyes from multi-dye systems using falling film photoreactor: performance evaluation, kinetic and toxicity analysis. Issue 6 (December 2020) - S.V., Manjunath; Tripathy, Binay Kumar; Kumar, Mathava; Pramod, Sreepriya
Graphical abstract: Highlights: Simultaneous removal of acidic and basic dye was investigated using falling film photoreactor. Concentration of dye(s) in multi-dye mixture was quantified using derivative spectroscopy. Effect of experimental conditions on dye(s) degradation was examined. Kinetic study, toxicity and dye degradation pathways were analyzed. Synergistic index, energy consumption and electrical energy order for dyes removal was assessed. Abstract: In this investigation, performance evaluation of different advanced oxidation processes (AOPs) viz. UV, PS, HPO, PS + HPO, UV + PS, UV + HPO and UV + PS + HPO in falling film photoreactor (FFPR) for degradation of methyl orange (MO) and eosin yellow (EY) dye(s) in mono-dye (MO/EY) and multi-dye (MO + EY) systems were examined. Meanwhile, the derivative spectroscopic method was used to quantify the concentration of dye(s) in multi-dye mixture. Subsequently, the effect of experimental conditions such as the reaction time, dye concentration and oxidant dosage on dye(s) degradation was studied. Furthermore, kinetic study, LCMS and toxicity study were carried out to determine the rate constant, degradation pathway and % inhibition, respectively. From the results, it was found that the UV + PS + HPO system was effective in the removal of both dyes in mono-dye and multi-dye systems. A maximum removal of 100% and 97.9% was noticed for MO and EY dyes in mono-dye system, respectively. Meanwhile, a maximum removal of 88.9% and 100% was seen for MO and EY dyes from MO + EY multi-dye system. On the other hand, the toxicity was found to decline after 240 min and 300 min of UV irradiation during the degradation of EY and MO dyes, respectively. The synergistic index, energy consumption and electrical energy order of UV + PS + HPO system were better for removal of dyes from mono-dye and multi-dye systems when compared with other AOPs. In general, UV + PS + HPO system in FFPR can be efficiently applied for the simultaneous removal of multiple dyes.